2021
DOI: 10.1017/s0007114521004724
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity, low dietary diversity and poor mental health among Syrian refugee mothers living in vulnerable areas of Greater Beirut, Lebanon

Abstract: Syrian refugees in Lebanon are facing vulnerabilities that are affecting their food insecurity levels. The objectives of this study were to measure dietary diversity, food insecurity (FI), and mental health status of Syrian refugee mothers in Lebanon and to explore its associations with their anemia and nutritional status. A cross-sectional study was conducted among mothers with children under 5 years (n=433) in Greater Beirut, Lebanon. Dietary diversity was measured using the Minimum Dietary Diversity for Wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 67 publications
(104 reference statements)
1
13
1
Order By: Relevance
“…In addition, Syrian refugees in Turkey reported that malnutrition and fatigue of mothers were often the biggest obstacles to breastfeeding [59]. These findings shed the light on the role of adequate maternal nutrition during pregnancy and lactation as it impacts the development and health of the offspring [75,76], which was particularly difficult to achieve among Syrian refugee mothers in Greater Beirut, Lebanon [17,18].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, Syrian refugees in Turkey reported that malnutrition and fatigue of mothers were often the biggest obstacles to breastfeeding [59]. These findings shed the light on the role of adequate maternal nutrition during pregnancy and lactation as it impacts the development and health of the offspring [75,76], which was particularly difficult to achieve among Syrian refugee mothers in Greater Beirut, Lebanon [17,18].…”
Section: Discussionmentioning
confidence: 93%
“…Crowded spaces were also reported to negatively impact breastfeeding practices among Syrian refugees in Lebanon [51]. This can be explained by the strong association between poor maternal mental health, food insecurity, and a high crowding index found among Syrian refugee mothers in Lebanon [18]. Particularly, stress related to conflicts was recognized as a major contributor to the discontinuation of breastfeeding among refugees and displaced persons, as it may interfere with the mother's let down reflex and lactation [1,44,46,51].…”
Section: Discussionmentioning
confidence: 99%
“…Low dietary diversity among mothers was also associated with higher odds of early initiation of breastfeeding. Poor dietary diversity was also linked to low income and food insecurity among Syrian refugee mothers in Greater Beirut, Lebanon [ 16 ]. This suggests that mothers facing increased economic vulnerabilities would be more inclined to initiate breastfeeding early as breast milk is known to be more cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Syrian refugees in Turkey reported that malnutrition and fatigue of mothers were often the biggest obstacles to breastfeeding [ 61 ]. These findings shed the light on the role of adequate maternal nutrition during pregnancy and lactation as it impacts the development and health of the offspring [ 77 , 78 ], which was particularly difficult to achieve among Syrian refugee mothers in Greater Beirut, Lebanon [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation